KELOMPOK STUDI PASAR MODAL (KSPM) LITERASI PASAR MODAL BAGI MAHASISWA INSTITUT SHANTI BHUANA - Dominggus; Jones Parlindungan Nadapdap; Dedy; Rissa Ayustia; Regina Clara Audrey Kaseger; Charley Orilya G. A. D. H. U (EDUKASI DAN PENGABDIAN MASYARAKAT, 2022)
The capital market has existed long before Indonesia's independence. Being an alternative with a very vital position in the development of the Indonesian economy, the capital market is also a source of funding for companies that need funds, apart from banking or through financial institutions that are involved in related industries. This community service is carried out with the aim of providing education about the capital market in the community through webinars, training for members of the Capital Market Study Group (KSPM) with the aim of being ready to provide knowledge about the capital market to the public and these activities have been carried out in the hope that they have knowledge about the capital market. capital market in the era of the industrial revolution 4.0. Changing people's mindsets to invest not only from one aspect, namely through the banking world, but also the capital market and not solely through bank loans, but through going public through the capital market. Based on the results of community service, it shows that to increase knowledge about the capital market to the community the Capital Market Study Group (KSPM) of the Shanti Bhuana Institute is to provide online and offline training to the community and KSPM members.